PHARMACOKINETIC DRUG- DRUG INTERACTIONS BETWEEN ALBUTEROL WITH BETA BLOCKERS TIMOLOL (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The present study was aimed to conduct to evaluate any possible pharmacokinetic interactions between albuterol and timolol. Study was conducted in Male Wistar rats; animals were divided in to three groups, Group I received albuterol alone in single dose / day in healthy rats. Group 2 received timolol alone in single dose / day in healthy rats. Group 3 received albuterol and timolol concomitant administration in healthy rats as a single dose / day. The treatment was given on day one and day 8 both alone albuterol and timolol concomitantly used both the drugs. There was no significant difference in both cmax, tmax and AUC0-t and AUCo-inf of albuterol alone and combination of timolol on day 1 and day 8 respectively. Based on the results obtained from kinetic study it is evident that the single dose of albuterol and timolol individually and concomitantly treated shows no statistically significant interactions in its pharmacokinetic parameters.